(untitled) (Comprehensive Journal of Science, 2026)
Offshore oil spills are among the most dangerous incidents for the marine environment because they result in environmental disasters that are not limited to the marine environment but extend to coastal countries and those who interact with this environment. Therefore, the problem addressed by this research lies in how toto set Responsibility for the risks posed by damaged ships to the marine environment Among these incidents is the Russian ship carrying large quantities of gas and its successors. The importance of this research lies in the search for the proper legal framework to address such incidents. Therefore, more of these studies are needed to demonstrate the shortcomings in determining who is responsible for these incidents and how to punish the perpetrators. The aim of this research is to identify international laws and treaties related to general and specific liability related to such incidents. Perhaps the interest in the marine environment is what motivates researchers to delve into such research. The researchers have reached conclusions, including that the perpetrators of such acts must be punished due to the multiplicity of narratives, some considering them acts of terrorism committed by some countries on behalf of the Russians, while the narrative of the other side does not direct any accusation at any individual, entity, institution, or country. The researchers recommend more of these studies and that deterrent legal rules be established for such acts, keeping them separate from political actions.